A NEW SPECIES OF GYROCHEILOS (GESNERIACEAE) FROM VIETNAM - Middleton, D. J. (Edinburgh Journal of Botany, 2015)
The new species Gyrocheilos orbiculatum D.J.Middleton (Gesneriaceae) is described and illustrated.